High risk-myelodysplastic syndrome following CAR T-cell therapy in a patient with relapsed diffuse large B cell lymphoma: A case report and literature review - Accorsi Buttini, Eugenia; Farina, Mirko; Lorenzi, Luisa; Polverelli, Nicola; Radici, Vera; Morello, Enrico; Colnaghi, Federica; Almici, Camillo; Ferrari, Emilio; Bianchetti, Andrea; Leoni, Alessandro; Re, Federica; et al. (Frontiers in Oncology, 2023)
Background: Chimeric antigen receptor (CAR) T-cell therapy represents the most advanced immunotherapy against relapsed/refractory B cell malignancies. While cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome are distinctive known CAR T-cell acute adverse events, hematological toxicity has been increasingly reported. Cytopenia following CAR T-cell treatment is attributed in most cases to the lymphodepletion regimens, bridging chemotherapy or radiotherapy. However, when cytopenia become prolonged the development of myelodysplastic syndrome (MDS) should be considered. Case presentation: We report a case of high risk (HR)-MDS following CAR T-cell therapy in a patient with relapsed diffuse large B cell lymphoma. Eight months after CAR T-cell infusion, blood count showed a progressive worsening cytopenia and the bone marrow biopsy revealed a multilineage dysplasia without excess of blasts associated with chromosome 7 deletion and RUNX1 mutation. The next generation sequencing analysis retrospectively performed on stored sample showed a germ line CSF3R mutation, CEBPA clonal hematopoiesis but not RUNX1 lesion. Conclusion: We described a case of HR-MDS with deletion of chromosome 7 and acquisition of RUNX1 mutation developing after CAR T-cell in a patient with clonal hematopoiesis (CH). The previous chemotherapy could favored the MDS onset but we couldn’t excluded that also the impairment of immunosurveillance related to either lymphodepletion and CAR T-cell infusion could played a role in the MDS development. Thus, we designed a multicenter prospective study (ClonHema-CAR-T-Study) in order to investigate if cytopenia after CAR T-cell treatment may be due to underling CH as well as the presence of secondary myeloid malignancies.